Gnsmood: um aplicativo web integrado ao ambiente virtual de aprendizagem que permite a comunicação de dispositivos de rede com o servidor de simulação gns3 - Silva, Isaias Batista da (Universidade Federal Rural do Semi-Árido, 2018)
The need to provide virtual laboratories with the objective of reinforcing the teaching of learning, especially in the áreas of geography, chemistry, physics, engineering and computing makes theorical-practical classes more interactive, contributing to learning significantly, regardless of geographical location. With the advancement of Information and Communication Technology (ICT) and the reality of data storage in the cloud, local operating systems and applications will tend to be incorporated and gradually virtualized to meet the cost and practical needs of institutions and users, respectively. From this new reality of applications and systems being integrated more and more to other platforms in the virtual world, with the aim of facilitating the sharing of infomation of these systems to meet a new emerging need of ICT’s to provide methodologies of distance learning more and more modern, this work was based on proposing to integrate the GNS3 simulator as a module of the Virtual Learning Environment (VLE). In this way, the practical activities during the discipline of computer networks in Distance Education (DE) courses will be supported, in order to make the practical classes of networks more dynamics and interactive. In addition to aplication portability, which in turn will allow it to be easily accessed from the URL on any computer device that supports the appropriate minimum processing and memory requirements
Keywords: Simulador GNS3; Ambiente virtual de aprendizagem (AVA); Educação a Distância (EaD); GNS3 simulator; Virtual learning environment (VLE); Distance education (DE); CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO